Characterization and in vitro antiparasitic activities of plant extracts containing natural and modified proanthocyanidins - Imran, Iqbal Bin (fi=Turun yliopisto|en=University of Turku|, 2023)
This thesis focused on the proanthocyanidins (PAs), a class of plant specialized metabolites that have a wide range of industrial applications. They play a vital role in the production of various food and feed products. Despite the abundance of natural PAs globally, many of them are still unexploited and could be used for various other industrial purposes. Further studies are needed to find ways to exploit these resources and make them useful for industrial purposes; this could include the extraction of PAs from plants and chemically modifying their structure to form other attractive products. The goal of this study was to investigate the possibility of modifying the natural PAs by studying their susceptibility to oxidation in alkaline conditions. This study investigated oxidized and non-oxidized PA-rich plant extracts from various plant kingdoms. It provides us to formulate a better understanding of PA oligomers and polymers in different PArich plants. The UHPLC-DAD-MS/MS method was used to provide these quantitative and qualitative data. The study revealed that the various structural features of PAs can be used to predict their susceptibility to oxidation. Overall, the results of the study revealed that the main reaction paths for procyanidins (PCs) and prodelphinidins (PDs) containing plant extracts were different under alkaline conditions. For instance, the former had an intramolecular route, while the latter had both intra and intermolecular reactions. Besides, the selected plant extracts were analyzed using orbitrap high-resolution mass spectrometry, which revealed the complex structural information and diverse reactions within the PA classes. Plant extracts were found to contain natural PAs from both A- and B-type structural families, as well as galloylated PAs. The A- and B-type PCs were relatively stable following oxidation, but some plant extracts produced new ether linkages. Conversely, PAs containing plant extracts that consisted only of PDs or PC/PD mixtures were found to be more reactive under alkaline conditions. Extracts rich in galloylated PCs were generally stable after oxidation, but those containing galloylated PDs or PC/PD mixtures were found to be more reactive. However, in certain cases, the addition of two or more galloyl groups to galloylated PCs increased their reactivity compared to those with only a single galloyl group. In addition, this study investigated the in vitro antiparasitic effects of various extracted Pas samples (original and oxidized) against Ascaris suum nematodes. The selected plant extracts were subjected to a detailed analysis of the antiparasitic properties by a highly reproducible in vitro larval migration inhibition assay. The modifications made to the PA-rich plant extracts significantly increased their antiparasitic activity. Some of the samples that showed no apparent antiparasitic activity prior to oxidation showed significant activity after the treatment and exhibited high levels of other polyphenols. Through the in vitro screening, we were able to gain a deeper understanding of how treating a plant with alkaline oxidation can improve its biological activity, which has the potential for novel anthelmintic drugs.